Cinderella and the Big Monster: Mail Art and the Museum. (3rd April 2017) - van der Meijden, Peter
Summary: Taking the difficulties involved in presenting Mail Art in a museum context as its point of departure, this article explores the conditions that Mail Art imposes on its own display. After a short introduction to the art form as a genre, two theoretical positions vis-à-vis Mail Art are analysed and shown to leave the matter of its communication with a secondary audience undiscussed. In order to arrive at a preliminary idea of the considerations involved, the discourse surrounding the new "relational" art of the 1990s (Nicolas Bourriaud, Claire Bishop, Jacques Rancière) is drawn upon to explore the question of whether a Mail Art display can be seen as an illustration of a specific form of communication, as a suggestion to a secondary audience to communicate differently or as a model of communication. Each step is accompanied by an analysis of one or more works: Ken Friedman's Omaha Flow Systems (1973), Niels Lomholt and Tom Elling's Mr. Klein- project (1978–1981), Rod Summers' VEC Secret Exchange and Operation Wipe Out (1976–1977) and Pierre Huyghe's and Philippe Parreno's No Ghost Just a Shell (1999–2002). The latter example, and especially the project's acquisition by the Van Abbemuseum in Eindhoven (NL) in 2002), is used to identify the distribution of tasks and functions within the museum as a central issue.